(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2021)
Among French-Italian literature there is a peculiar chanson de geste: the Huon d’Auvergne. The chanson narrates the long journey of the paladin Huon to reach Hell: this itinerary takes place, in part, on water. For Huon, the sea has different meanings, which the article tries to highlight through the analysis of some salient episodes. On the one hand, the sea element represents the Christian punishment for sinners, namely the pirates who abandon Huon immediately after leaving Libya. On the other hand, the sea is generally understood as the place of the manifestation of the divine, who exercises his merciful and, at the same time, punishing power. During the article, an attempt will be made to highlight the role and presence of the Christian wonder during the Count of Auvergne’s itinerary, with particular reference to the marine element.